1990
DOI: 10.1042/bj2720181
|View full text |Cite
|
Sign up to set email alerts
|

The effect of (−)-hydroxycitrate on the activity of the low-density-lipoprotein receptor and 3-hydroxy-3-methylglutaryl-CoA reductase levels in the human hepatoma cell line Hep G2

Abstract: (-)-Hydroxycitrate, a potent inhibitor of ATP citrate-lyase, was tested in Hep G2 cells for effects on cholesterol homoeostasis. After 2.5 h and 18 h incubations with (-)-hydroxycitrate at concentrations of 0.5 mM or higher, incorporation of [1,5-14C]citrate into fatty acids and cholesterol was strongly inhibited. This most likely reflects an effective inhibition of ATP citrate-lyase. Cholesterol biosynthesis was decreased to 27% of the control value as measured by incorporations from 3H2O, indicating a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Hood et al (1985) provided the in vitro inhibitory effect of HCA on the conversion of lactate, acetate and glucose to fatty acids in bovine and rat adipose tissues. HCA also inhibited the incorporation of C 14 labeled citrate into fatty acids and cholesterol in Hep G2 cells after 18 h of incubation (Berkhout et al 1990). These studies suggested the beneficial properties of HCA in the weight management by interfering in the fatty acid biosynthesis and cholesterol homeostasis.…”
Section: Pericarpmentioning
confidence: 94%
“…Hood et al (1985) provided the in vitro inhibitory effect of HCA on the conversion of lactate, acetate and glucose to fatty acids in bovine and rat adipose tissues. HCA also inhibited the incorporation of C 14 labeled citrate into fatty acids and cholesterol in Hep G2 cells after 18 h of incubation (Berkhout et al 1990). These studies suggested the beneficial properties of HCA in the weight management by interfering in the fatty acid biosynthesis and cholesterol homeostasis.…”
Section: Pericarpmentioning
confidence: 94%
“…Pharmacological inhibition of ACL has been shown to limit sterol and fatty acid synthesis ( 40,(43)(44)(45)(46), upregulate LDL receptor activity ( 47 ), and reduce plasma triglycerides and cholesterol levels ( 45,48 ). Furthermore, liverspecifi c ACL abrogation results in reduced levels of liver Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was applied to a Bond-Elut NH 2 column and eluted with 1 ml of toluene/acetone (3:1). The eluate was discarded and an additional 4 ml of toluene/acetone was applied to the column and collected in a scintillation vial for counting 14 C and 3 H signals (Berkhout et al, 1990).…”
Section: Methodsmentioning
confidence: 99%